The grapes of wrath and other writings 1936 - 1941 - Steinbeck, John 1902-1968 (Library of America, 1996)
From the Publisher: This second volume in The Library of America's authoritative edition of John Steinbeck features his acknowledged masterpiece, The Grapes of Wrath. Written in an incredibly compressed five-month period, the novel had an electrifying impact upon publication in 1939, unleashing a political storm with its vision of America's dispossessed struggling for survival. It continues to exert a powerful influence on American culture, and has inspired artists as diverse as John Ford, Woody Guthrie, and Bruce Springsteen. Tracing the journey of the Joad family from the dust bowl of Oklahoma to the migrant camps of California, Steinbeck creates an American epic, spacious, impassioned, and pulsating with the rhythms of living speech. The novel won the Pulitzer Prize and has since sold millions of copies worldwide. The text of The Grapes of Wrath has been newly edited based on Steinbeck's manuscript, typescript, and proofs
Enth. u.a.: The long valley. The grapes of wrath
Keywords: Fauna marina - Mexico - California, Golfo de; Migración de trabajadores agrícolas - California, EE. UU - Condiciones sociales; Alltag, Brauchtum; Migrant agricultural laborers -- California -- Social conditions; Migrant agricultural laborers -- Fiction; Marine invertebrates -- Mexico -- California, Gulf of; Rural families -- Fiction; Depressions -- Fiction; Landarbeiter; Weltwirtschaftskrise -- 1929-1932; Auswanderung; California, Golfo de - Descripción y viajes; Mexiko; Salinas River Valley (Calif.) -- Social life and customs -- Fiction; California, Gulf of (Mexico) -- Description and travel; Kalifornien; Oklahoma; Fiktionale Darstellung